2014
DOI: 10.1038/srep06188
|View full text |Cite
|
Sign up to set email alerts
|

A crystal structure-guided rational design switching non-carbohydrate inhibitors' specificity between two β-GlcNAcase homologs

Abstract: Selective inhibition of function-specific β-GlcNAcase has great potential in terms of drug design and biological research. The symmetrical bis-naphthalimide M-31850 was previously obtained by screening for specificity against human glycoconjugate-lytic β-GlcNAcase. Using protein-ligand co-crystallization and molecular docking, we designed an unsymmetrical dyad of naphthalimide and thiadiazole, Q2, that changes naphthalimide specificity from against a human glycoconjugate-lytic β-GlcNAcase to against insect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…Palmatine without the 1,3-dioxole group showed a K i value for OfHex1 that was more than 4-fold higher than that of berberine (Table 1). Notably, this hydrophobic recess has not been occupied by other (42).…”
Section: Crystal Structure Of Ofhex1 In Complex With Berberinementioning
confidence: 99%
See 1 more Smart Citation
“…Palmatine without the 1,3-dioxole group showed a K i value for OfHex1 that was more than 4-fold higher than that of berberine (Table 1). Notably, this hydrophobic recess has not been occupied by other (42).…”
Section: Crystal Structure Of Ofhex1 In Complex With Berberinementioning
confidence: 99%
“…In the previous work, we noticed that compounds with a large conjugated plane were highly potent inhibitors of GH20 Hex (21,42) and GH18 chitinase (39). Berberine is a typical compound with a large conjugated plane.…”
mentioning
confidence: 96%
“…In addition, compound Q1 ( 8 ) shows inhibitory potency against GH20 insect β- N -acetylhexosaminidase OfHex1 with K i values of 4.28 µM. The complex crystal structure of OfHex1 -Q1 (PDB ID: 3WMB) reveals that the methylthiadiazole group of Q1 binds the −1 subsite of OfHex1, whereas the napthalimide group is sandwiched by the amino acid residues of the +1 subsite (outside of −1 subsite) 23 .…”
Section: Introductionmentioning
confidence: 99%
“…24 To improve the selective inhibition against OfHex1, Q2 (4) bearing a 4-dimethylamino group on the naphthalimide unit was designed and exhibited K i values of 0.3 μM against OfHex1 and more than 100 μM against HsHex. 24 The complex crystal structure of OfHex1-Q1 (PDB: 3WMB) and OfHex1-Q2 (PDB: 3WMC) revealed that the 4-dimethylaminonaphthalimide moiety of Q2 rotates approximately 180°(relative to naphthalimide moiety of Q1) and is tightly bound to the +1 subunit of OfHex1 via π−π stacking with Trp490. 24 However, relative to Q1 the added dimethylamino group led to an increase in the steric hindrance for Q2 to bind the −1 subsite of HsHex.…”
mentioning
confidence: 99%
“…24 The complex crystal structure of OfHex1-Q1 (PDB: 3WMB) and OfHex1-Q2 (PDB: 3WMC) revealed that the 4-dimethylaminonaphthalimide moiety of Q2 rotates approximately 180°(relative to naphthalimide moiety of Q1) and is tightly bound to the +1 subunit of OfHex1 via π−π stacking with Trp490. 24 However, relative to Q1 the added dimethylamino group led to an increase in the steric hindrance for Q2 to bind the −1 subsite of HsHex. 24 These results suggest that the 4-substituent at naphthalimide moiety may be crucial for the activity and selectivity of β-N-acetylhexosaminidases in the naphthalimides (Figure 1).…”
mentioning
confidence: 99%